2021
DOI: 10.1155/2021/6697810
|View full text |Cite|
|
Sign up to set email alerts
|

Shared Genetic and Epigenetic Mechanisms between the Osteogenic Differentiation of Dental Pulp Stem Cells and Bone Marrow Stem Cells

Abstract: Objective. To identify the shared genetic and epigenetic mechanisms between the osteogenic differentiation of dental pulp stem cells (DPSC) and bone marrow stem cells (BMSC). Materials and Methods. The profiling datasets of miRNA expression in the osteogenic differentiation of mesenchymal stem cells from the dental pulp (DPSC) and bone marrow (BMSC) were searched in the Gene Expression Omnibus (GEO) database. The differential expression analysis was performed to identify differentially expressed miRNAs (DEmiRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 100 publications
0
15
1
Order By: Relevance
“…13 A previous study has demonstrated that naringin facilitates osteogenic differentiation of bone mesenchymal stem cells (BMSCs), thus facilitating bone formation and alleviating osteoporosis in ovariectomy (OVX)-induced osteoporotic mice. 14 Previously, naringin was reported to exert protective effects against ankylosing spondylitis in mice via the induction of ossification, suppression of oxidative stress and inflammation, which were mediated by the inhibition of the Janus activated kinase 2 (JAK2)/signal transducer and the activator of transcription 3 (STAT3) pathway. 15 The JAK2/STAT3 pathway was shown to play a pivotal role in the initiation and development of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…13 A previous study has demonstrated that naringin facilitates osteogenic differentiation of bone mesenchymal stem cells (BMSCs), thus facilitating bone formation and alleviating osteoporosis in ovariectomy (OVX)-induced osteoporotic mice. 14 Previously, naringin was reported to exert protective effects against ankylosing spondylitis in mice via the induction of ossification, suppression of oxidative stress and inflammation, which were mediated by the inhibition of the Janus activated kinase 2 (JAK2)/signal transducer and the activator of transcription 3 (STAT3) pathway. 15 The JAK2/STAT3 pathway was shown to play a pivotal role in the initiation and development of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…The miR-146 family is highly conserved between fish and humans, and it shares the same seed sequence [52]. In humans, it has been demonstrated that miR146b is downregulated in both bone marrow stem cell (BMSC) chondrogenesis [53] and osteogenesis [54]. In addition, it has been demonstrated that miR146b promotes adipogenesis too [55].…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects, i.e., enhanced mineralization and ALP activity with minimal (<50%) or no significant changes in osteogenic gene expression, have been previously reported in MC3T3-E1 osteoblasts treated with zinc and genistein [ 60 ]. Furthermore, curcumin appears to play a role as an epigenetic modulator in general [ 43 ] and specifically as an epigenetic modulator of miRNAs involved in the osteogenic differentiation of dental pulp stem cells [ 43 , 61 ]. Going forward, we suggest focusing on the mechanisms by which the three nutraceuticals studied can improve bone health in microgravity, for example, by altering post-translational regulation of the transcriptional activity of osteogenic genes or serving as modulators of the epigenetics of osteogenic miRNAs.…”
Section: Discussionmentioning
confidence: 99%